Schistosomiasis Presenting as a Case of Acute Appendicitis with Chronic Mesenteric Thrombosis - Mohammed H. Mosli; Wilson W. Chan; Izabella Morava-Protzner; Susan M. Kuhn (Canadian Journal of Infectious Diseases and Medical Microbiology)
The manifestations of schistosomiasis typically result from the host inflammatory response to parasitic eggs that are deposited in the mucosa of either the gastrointestinal tract or bladder. We present here a case of a 50-year-old gentleman with a rare gastrointestinal presentation of both schistosomal appendicitis and mesenteric thrombosis.